"No One, Not Even God, Can Take the Place of the Victim": Metz, Lévinas, and Practical Christology after the Shoah - Simon, Derek (Horizons, 1999)
The legacy of the Shoah invades christology as one of its most basic postfoundationalist challenges in the demise of modernity. Fackenheim heuristically amplifies the rupture of the metaphysical narratives of soteriology by the radical evil and sufferings in Auschwitz. As a representative instance of reorienting theological discourse through exposure to the trauma of the Shoah and the testimony of its Jewish survivors, Metz grounds practical christology in the biblical memory of suffering and an eschatological delimitation of time. Lévinas' phenomenology of the self counters residual issues in Metz and mediates a postfoundationalist framework for re-visioning christology after the Shoah. The phenomenological transposition of the notion of substitution to the ethical order rehabilitates Metz's practical christology and articulates the messianic significance of human agency as a sociopolitical responsibility for the sufferings of the broken and the dead.